On‐Site Melanoma Diagnosis Utilizing a Swellable Microneedle‐Assisted Skin Interstitial Fluid Sampling and a Microfluidic Particle Dam for Visual Quantification of S100A1 - Gaobo Wang; Yuyue Zhang; Hoi Kwan Kwong; Mengjia Zheng; Jianpeng Wu; Chenyu Cui; Kannie W. Y. Chan; Chenjie Xu; Ting‐Hsuan Chen (Advanced Science, 2024)
Abstract Malignant melanoma (MM) is the most aggressive form of skin cancer. The delay in treatment will induce metastasis, resulting in a poor prognosis and even death. Here, a two‐step strategy for on‐site diagnosis of MM is developed based on the extraction and direct visual quantification of S100A1, a biomarker for melanoma. First, a swellable microneedle is utilized to extract S100A1 in skin interstitial fluid (ISF) with minimal invasion. After elution, antibody‐conjugated magnetic microparticles (MMPs) and polystyrene microparticles (PMPs) are introduced. A high expression level of S100A1 gives rise to a robust binding between MMPs and PMPs and reduces the number of free PMPs. By loading the reacted solution into the device with a microfluidic particle dam, the quantity of free PMPs after magnetic separation is displayed with their accumulation length inversely proportional to S100A1 levels. A limit of detection of 18.7 ng mL−1 for S100A1 is achieved. The animal experiment indicates that ISF‐based S100A1 quantification using the proposed strategy exhibits a significantly higher sensitivity compared with conventional serum‐based detection. In addition, the result is highly comparable with the gold standard enzyme‐linked immunosorbent assay based on Lin's concordance correlation coefficient, suggesting the high practicality for routine monitoring of melanoma.